Consider Hereditary Angioedema in the Differential Diagnosis for Unexplained Recurring Abdominal Pain. Issue 9 (15th October 2022) - Staller, Kyle; Lembo, Anthony; Banerji, Aleena; Bernstein, Jonathan A.; Shah, Eric D.; Riedl, Marc A.
Abstract : Health care providers are likely to encounter patients with recurrent unexplained abdominal pain. Because hereditary angioedema (HAE) is a rare disease, it may not be part of the differential diagnosis, especially for patients who do not have concurrent skin swelling in addition to abdominal symptoms. Abdominal pain is very common in patients with HAE, occurring in up to 93% of patients, with recurrent abdominal pain reported in up to 80% of patients. In 49% of HAE attacks with abdominal symptoms, isolated abdominal pain was the only symptom. Other abdominal symptoms that commonly present in patients with HAE include distension, cramping, nausea, vomiting, and diarrhea. The average time from onset of symptoms to diagnosis is 6 to 23 years. Under-recognition of HAE in patients presenting with predominant gastrointestinal symptoms is a key factor contributing to the delay in diagnosis, increasing the likelihood of unnecessary or exploratory surgeries or procedures and the potential risk of related complications. HAE should be considered in the differential diagnosis for patients with unexplained abdominal pain, nausea, vomiting, and/or diarrhea who have complete resolution of symptoms between episodes. As highly effective targeted therapies for HAE exist, recognition and diagnosis of HAE in patients presenting with isolated abdominal pain may significantly improve morbidity and mortality for these individuals.